2013
DOI: 10.5296/jse.v3i2.3371
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Setting Accommodation on Large-scale Assessment of English Language Learners with and without Learning Disabilities: Balanced vs. Unbalanced Data in Latent Class Analyses

Abstract: This exploratory study examined the effect of setting accommodation on Grade 6 students' number sense and numeration skill in relation to whether they speak a language other than English at home, have a learning disability, and received setting accommodation for a large-scale math assessment. A set of latent class analyses was conducted to investigate students' response patterns and latent class memberships in both balanced and unbalanced data; three-and two-way ANOVA were also performed to examine the effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Smith and Riccomini (2013) reported that students with learning disabilities in grades 3 to 5 demonstrated greater improvement in reading comprehension relative to their typically developing peers when wearing noise-reducing headphones. In contrast, Lin and Lin (2013) found that students with learning disabilities did not benefit from a reduced noise environment when tested on number sense and numeration skills.…”
Section: Introductionmentioning
confidence: 80%
“…Smith and Riccomini (2013) reported that students with learning disabilities in grades 3 to 5 demonstrated greater improvement in reading comprehension relative to their typically developing peers when wearing noise-reducing headphones. In contrast, Lin and Lin (2013) found that students with learning disabilities did not benefit from a reduced noise environment when tested on number sense and numeration skills.…”
Section: Introductionmentioning
confidence: 80%
“…Smith and Riccomini [ 67 ] reported that students with learning disabilities in grades 3 to 5 demonstrated greater improvement in reading comprehension relative to their typically developing peers when wearing noise-reducing headphones. Contradicting this, Lin and Lin [ 45 ] found that students with learning disabilities did not benefit from a reduced noise environment when tested on number sense and numeration skills. Closest to our target population, Nelson and Lovett [ 49 ] administered two parallel forms of a timed silent reading comprehension test to a sample of college students with ADHD, one in a classroom with other students, and one in a private, proctored setting.…”
Section: Related Workmentioning
confidence: 99%
“…Examples of setting accommodations include preferential seating, special lighting, and accessible workstations. Martha and Cathryn (2008) and Lin and Lin (2013) have both highlighted the importance of such changes in ensuring equitable and inclusive educational environments. Martha and Cathryn (2008) found evidence of regular scheduling accommodations to increase available test or assignment time and alter time allotment.…”
Section: Inclusive Education School Assessment Accommodations For Lea...mentioning
confidence: 99%